The Effectiveness of Islamic Religious Education Teaching Management in the Development of Characteristics in Students - Arifin, Syamsul (Devotion : Journal of Research and Community Service, 2022)
The phenomenon of the decline in the morals of the nation's generation, including the nation's elite, often becomes an apology for some people to give scathing criticism of educational institutions. This is very reasonable because education actually has a very basic mission, namely to form a complete human being with morals as one of the main indicators, the nation's generation with noble character is one of the profiles expected from the practice of national education. The purpose of this study was to obtain a clear picture and an in-depth analysis of the effectiveness of the teaching management of Islamic Religious Education in moral development at SDN Cibabat Mandiri 3 and SDN Cibabat 4 . In this study, researchers generally use descriptive qualitative research methods through observation, interviews, document review, questionnaires and other media. In analyzing the data, the researcher uses Miles and Hubermen's theory which consists of three activity lines, namely data reduction, data presentation, and conclusion drawing or verification. Based on results research at SDN Cibabat Mandiri 3 and SDN Cibabat 4 Cimahi City could drawn conclusion that effectiveness management PAI teaching in construction morals in students has apply principles and goals management education, start with apply planning, implementation, and evaluation in every activity as well as the programs presented. This thing impact positive on every activity classroom teaching and outside class moment PAI teaching is carried out nor in construction morality in students.